PENGARUH ASIMETRI INFORMASI DAN PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP PRAKTIK MANAJEMEN LABA DI BURSA EFEK INDONESIA - B2041141019, MARTINUS YOPI SUSANTO (Universitas Tanjungpura, 2017)
The purpose of this study is to investigate the relationship of information asymmetry, implementation of good corporate governance and earnings management practices in Indonesian Stock Exchange. Information asymmetry measured by using bid ask spread, whereas the practice of good corporate governance proxies by the proportion of independent board, audit committee existence and audit quality. This study is an econometric study by using panel data that taken from the Indonesian Stock Exchange with 22 companies from the property and real estate subsector during the period 2012, 2013 and 2014 as samples which were selected by using purposive sampling method. Moreover, the analysis method of this study is multiple regression. Hypothesis testing results showed there is a significant negative relation between audit quality and earnings management practices. It means that the higher quality audit performed by the independent auditor may reduce the earnings management practices in the company. Furthermore, information asymmetry, the proportion of independent board and audit committee has not proven a significant relation with earnings management practices. Keywords: Earnings management, asymmetry information, good corporate governance, the proportion of independent board, audit committee, audit quality